2019
DOI: 10.1038/s41598-019-44530-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maize rotation on the physicochemical properties and microbial communities of American ginseng cultivated soil

Abstract: The production of American ginseng ( Panax quinquefolius L.) is severely limited by the replant disorders in China. Crop rotation with maize might reduce the replant problems, but little information is available on the effect of maize rotation on soil cultivated with ginseng. In this study, we analyzed nutrients, phenolic acids, and microbial communities in soils from the fields with continuous maize, mono-culture ginseng, and 1-, 3-, and 5-year maize rotation after ginseng. Pot experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…However, due to the lack of arable land in Jiaozuo City, R. glutinosa is frequently replanted in the same field at intervals of less than 8 years, or cultivated beyond its geo-authentic region to meet market demand, resulting in a high incidence of disease, lower tuber yield, and poor product quality. Similar situations are also observed in other geo-authentic herbal plants (e.g., Panax ginseng and Panax notoginseng ) ( Yang et al, 2015 ; Dong et al, 2018a , b ), which has severely hindered the production of medicinal products and sustainable development of traditional Chinese medicines ( Gao et al, 2006 ; Zhang and Lin, 2009 ; Kong et al, 2011 ; Jiao et al, 2019 ). Given the serious replanting issues associated with production, R. glutinosa has been regarded as a model species for the study of replanting problems in perennial herbal plants ( Zhang and Lin, 2009 ).…”
Section: Introductionsupporting
confidence: 55%
“…However, due to the lack of arable land in Jiaozuo City, R. glutinosa is frequently replanted in the same field at intervals of less than 8 years, or cultivated beyond its geo-authentic region to meet market demand, resulting in a high incidence of disease, lower tuber yield, and poor product quality. Similar situations are also observed in other geo-authentic herbal plants (e.g., Panax ginseng and Panax notoginseng ) ( Yang et al, 2015 ; Dong et al, 2018a , b ), which has severely hindered the production of medicinal products and sustainable development of traditional Chinese medicines ( Gao et al, 2006 ; Zhang and Lin, 2009 ; Kong et al, 2011 ; Jiao et al, 2019 ). Given the serious replanting issues associated with production, R. glutinosa has been regarded as a model species for the study of replanting problems in perennial herbal plants ( Zhang and Lin, 2009 ).…”
Section: Introductionsupporting
confidence: 55%
“…For instance, the continuous corn showed relatively less soil K contents than the soils under crop rotation systems at three northern corn/soybean belt locations in the United States [207]. Jiao et al (2019) reported that soil under American ginseng showed relatively higher micronutrients such as manganese (Mn), copper (Cu), and iron (Fe) being 113%, 99%, and 80% higher than in the soil of continuously cultivated maize crop [251]. Moreover, the CC under certain standard practices may create obnoxious conditions under which plants may not take up sufficient nutrients from the soil, which may also lead to reduced plant growth and crop yield [84,252].…”
Section: Soil Physicochemical Properties and Nutrient Deficienciesmentioning
confidence: 99%
“…Some studies have reported that the quality of American ginseng differs considerably depending on the age and cultivation region [14,15]. In addition, the application of biofertilisers has also shown to decrease the rate of rotten roots, thus enhancing the yield and quality [16][17][18]. However, most researches are focused on the root, and only the MR is popular among consumers [19].…”
Section: Introductionmentioning
confidence: 99%